2008
DOI: 10.1093/ije/dyn154
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age and risk factors for cardiovascular disease: evidence from the 1958 British birth cohort followed to mid-life

Abstract: In the 1958 British birth cohort duration of gestation was associated with blood pressure in mid-life. Understanding this association is necessary to inform policy and preventative interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 41 publications
(67 reference statements)
2
57
1
Order By: Relevance
“…Similar findings were reported in a study of young adults; a lower GFR, higher serum creatinine and microalbuminaria was reported at 19 years of age in subjects born at <32 weeks gestation (and also small for gestational age) [54]. Furthermore, there is strong epidemiological evidence to link premature birth with the development of hypertension [58][59][60][61][62][63] and increased cardiovascular risk during adulthood [64,65]. This 'risk' may be further exacerbated in the presence of impaired renal function, possibly leading to hypertension, and the possible development of cardiovascular disease in later life [66].…”
Section: Renal Functionsupporting
confidence: 83%
“…Similar findings were reported in a study of young adults; a lower GFR, higher serum creatinine and microalbuminaria was reported at 19 years of age in subjects born at <32 weeks gestation (and also small for gestational age) [54]. Furthermore, there is strong epidemiological evidence to link premature birth with the development of hypertension [58][59][60][61][62][63] and increased cardiovascular risk during adulthood [64,65]. This 'risk' may be further exacerbated in the presence of impaired renal function, possibly leading to hypertension, and the possible development of cardiovascular disease in later life [66].…”
Section: Renal Functionsupporting
confidence: 83%
“…Gestational age, included because recent evidence suggests that this may be associated with cardiovascular disease risk factors, [18][19][20] was recorded as days since the start of last menstrual period at birth and converted into weeks. Height at age 7y was measured during medical examinations.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, aortic narrowing was reported in adolescents who were born preterm (7). Arterial narrowing is likely to be detrimental in the long term and may contribute to the now well-described elevation in arterial pressure in subjects born preterm (2)(3)(4)(5)8,9,31).…”
Section: Aortic Structure and Compositionmentioning
confidence: 99%
“…As a result of advances in neonatal care, most preterm infants survive infancy, even those born as early as 23 wk (1). Epidemiological studies have linked preterm birth to hypertension and vascular abnormalities in children and young adults (2)(3)(4)(5)(6)(7)(8)(9); the risk is increased with decreasing gestational age at birth, suggestive of causality (2,3,6). For example, one study found a 0.31 mm Hg increase in adult blood pressure for every week of prematurity (2).…”
mentioning
confidence: 99%